ANALISIS PELAKSANAAN PELAYANAN ANC TERPADU DI PUSKESMAS TEMBILAHAN HULU: implementation of ante natal care 10 standards and obstacles in their implementation - sandra harianis; Mia Rita Sari; Dewi Erlina Asrita Sari; Madinah Madinah (STIKes Al-Insyirah Pekanbaru, 2019)
Abstract The health of pregnant women is still a national health problem. Ante Natal Care (ANC) services integrated with 10 standards can improve maternal and fetal health. However, in recent years complications of pregnancy and childbirth have increased which should be identified early with the right ANC. This study aims to explore the implementation of ANC 10 standards and obstacles in their implementation. This study uses a qualitative design with a phenomenological approach. The study began with qualitative data collection through focus group discussion (FGD) and in-depth interviews and quantitative data collection through filling out questionnaires in October-November 2018 in the working area of ​​the Upper Tembilahan Health Center. The sample of this study was all midwives at the Tembilahan Hulu health center and pregnant women were randomly taken as many as 138 people. The findings of this study note 35 out of 138 (25.4%) pregnant women received standard ANC 10 services in full. Weigh BB and measure TB (86.23%), measure blood pressure (100%), nutritional status (88.41%), measure TFU (85.51%), value of fetal presentation (81.88%), srining T (81.16%), Fe tablets (71.01%), labor checks (81.88%), case management (82.61%), and speech meetings (69.57%). The obstacle of midwives is inadequate facilities and infrastructure and the weak skills of midwives in implementing standards. The need for monitoring and evaluation of KIA program holders and guidance and training for integrated ANC servants for all midwives